NOVEL CINTA DI UJUNG SAJADAH KARYA ASMA NADIA: ANALISIS EKSISTENSI PEREMPUAN - Widya Arieska; Nurizzati Nurizzati; Zulfadhli Zulfadhli (Faculty of Languages and Arts, Universitas Negeri Padang, 2014)
This study is a qualitative study using descriptive methods. Object of this research is the novel Cinta di Ujung Sajadah of Asma Nadia a novel family first printing, July 2012. Data collected with the following steps: (1) read and understand the novel, (2) marking the parts that indicate the existence of women in novel, (3) identify the nature of the character corresponding to the research problem, (4) to classify sentences and paragraphs that can show a picture of women in the novel. Data were analyzed with the following steps: (1) describe a novel structure, (2) interpret the existence of women as reflected in the figures of women in the novel, (3) concluded that the data has been analyzed and interpreted, and (4) report the results of research. Based on the analysis of data it can be concluded that the existence of the female characters in the novel Cinta di Ujung Sajadah of Asma Nadia works are grouped as follows. (1) The existence of women as a person is having a hard-hearted personality, has the establishment, independent, religious, and faithful, (2) the existence of women as members of the family are affectionate, patient nature, gentle, (3) the existence of women as members of the community is a concern for other people, the environment and other people's relationships, respect for others, and gregarious.